Analisis kemampuan metakognitif siswa dalam pemecahan masalah matematika materi program linear ditinjau dari gaya belajar (Prosiding Seminar Nasional Matematika dan Pendidikan Matematika, 2021)
This research aims to describe students' metacognitive abilities in solving mathematical problems on linear programs material in terms of learning styles. The research method used is descriptive qualitative. Subjects in this study are class XI MIPA 1 SMA Negeri 1 Weleri using purposive sampling will be selected by at least one student from each learning style. The results are: students with visual, auditory, and kinesthetic learning styles bring up indicators in metacognitive aspects, namely planning, monitoring, and evaluation. However, students with kinesthetic learning styles in the evaluation aspect raise 2 out of 4 indicators. The factors that influence the emergence of students' metacognitive abilities in solving mathematical problems for each learning style are differences in student characteristics and the suitability of teaching styles and learning styles.
Keywords: metacognitive ability; problem solving; linear programs; learning styles